Sliding free transverse rectus abdominis myocutaneous flap for closure of a massive abdominal wall defect: a case report - Senghaas, Annika; Kremer, Thomas; Schmidt, Volker-Jürgen; Harhaus-Wähner, Leila; Hirche, Christoph; Kneser, Ulrich; Bigdeli, Amir Khosrow (Microsurgery, 2019)
Despite considerable advances in reconstructive surgery, massive abdominal wall defects continue to pose a significant surgical challenge. We report the case of a 72-year-old morbidly obese female patient with Clostridium septicum-related gas gangrene of the abdominal wall. After multidisciplinary treatment and multiple extensive debridements, a massive full-thickness defect (40 cm × 35 cm) of the right abdominal wall was present. The abdominal contents were covered with a resorbable mesh to prevent evisceration. Finally, the composite defect was successfully reconstructed through a contralateral extended free transverse rectus abdominis myocutaneus (TRAM) flap (50 cm × 38 cm). An arterio-venous loop to the superficial femoral vessels using the great saphenous vein was necessary to allow the flap to reach the defect. Postoperatively, a minor wound healing disorder of the flap was successfully treated with split skin grafting. Six month after surgery, the patient presented with a completely healed flap coverage area and a small abdominal hernia without the need of further surgical revision. This case illustrates the use of a sliding free TRAM flap for closure of a massive abdominal wall defect.